Relapse Rate in Pediatric-Onset Multiple Sclerosis - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2009)
Relapse rates were compared during 12 months or longer follow-up between 21 pediatric onset cases of multiple sclerosis (MS) seen at the Massachusetts General and 110 patients with adult-onset MS at the Brigham and Women's Hospitals, Boston, MA.